Development of 2-arylbenzo[h]quinolone analogs as selective CYP1B1 inhibitors. Issue 27 (20th April 2018) - Dong, Jinyun; Wang, Zengtao; Meng, Qingqing; Zhang, Qijing; Huang, Guang; Cui, Jiahua; Li, Shaoshun
Abstract : 2-arylbenzo[ h ]quinolin-4(1 H )-ones are developed as selective CYP1B1 inhibitors. Abstract : The CYP1B1 enzyme is regarded as a potential target for cancer prevention and therapy. Based on the structure of α-naphthoflavone (ANF), diverse 2-arylbenzo[ h ]quinolone derivatives were designed, synthesized and evaluated as selective CYP1B1 inhibitors. Compared with ANF, although few of the title compounds possessed comparable or slightly higher CYP1B1 inhibitory activity, these compounds displayed a significantly increased selectivity toward CYP1B1 over CYP1A2. Among them compounds5e, 5g and5h potently inhibited the activity of CYP1B1 with IC50 values of 3.6, 3.9 and 4.1 nM respectively, paralleled by an excellent selectivity profile. On the basis of predicted clog  P values, these target compounds may exhibit improved water-solubility compared to ANF. In particular, 5h showed a great superiority in the reversal of CYP1B1-mediated docetaxel resistance in vitro . The current study may serve as a good starting point for the further development of more potent as well as specific CYP1B1 inhibitors capable of reversing CYP1B1-mediated anticancer-drug resistance.